The The Impact of Mental Health Training Interventions on Cadres' Ability to Detect Depression Among Rural Elderly - Kurnia, Anna; Nur Hidayati, Tri; Ariyana Rahayu, Desi; Yusuf, Ah; Indarwati, Retno; Chia-Jung Hsieh (Window of Health : Jurnal Kesehatan, 2025)
Depression is a prevalent concern among the elderly population, potentially leading to suicidal ideation and behavior. Consequently, proactive measures are imperative to mitigate depression's impact. Community cadres, who offer voluntary assistance to healthcare professionals, play a crucial role in the early detection of depression. This study aims to evaluate the efficacy of a training program designed for cadres in identifying depression among elderly individuals residing in rural areas. This study utilized purposive random sampling to employ a pre-experimental design with a single-group pre-post intervention. 89 participants meeting the inclusion criteria—being mental health cadres and having completed comprehensive training—were randomly assigned. The intervention involved training participants in recognizing depression symptoms in the elderly. Data was collected using a personal information form and a questionnaire assessing the ability to detect early signs of depression in the elderly, administered before and after the intervention. Statistical analyses were conducted using SPSS-22, employing paired t-tests and Chi-square tests. The findings indicate a significant improvement in the cadres' ability to identify depression among rural elderly individuals following the intervention (p = 0.005). This study underscores the effectiveness of training programs in enhancing cadres' proficiency in recognizing depression among elderly rural residents. Consequently, we advocate for integrating regular mental health training sessions for community cadres within public health initiatives.